Nilai Pendidikan Karakter Religius Novel Sawitri dan Tujuh Pohon Kelahiran Karya Mashdar Zainal: Perspektif Tradisi Islam Nusantara - Chandra, Afry Adi; Waluyo, Herman J; Wardani, Nugraheni Eko (Jurnal Lektur Keagamaan, 2019)
This article describes the educational value of the religious character in the novel of Sawitri and the Seven Birth Trees (Sawitri dan Tujuh Pohon Kelahiran) by Mashdar Zainal based on the perspective of the Islam Nusantara tradition. The existence of the value of religious character education is a very important aspect to internalize the students, as an effort to shape the distinctive character of the Indonesian nation. The acculturation between Javanese culture and Islamic tradition has had a major impact on the life of the Javanese people. The acculturation process had a positive impact on both, both for the development of Islam and Javanese culture. The main data source of this research is the text in the novel of Sawitri and the Seven Birth Trees (Sawitri dan Tujuh Pohon Kelahiran) which relates to the value of character education based on the perspective of the Islamic Nusantara tradition. Data collection techniques use content analysis. Data validity techniques using data source triangulation and method triangulation. The flow models of Miles and Huberman, namely data reduction, data presentation, and conclusion and verification are used as techniques for analyzing data. The results of the study show in the novel of Sawitri and the Seven Birth Trees (Sawitri dan Tujuh Pohon Kelahiran) by Mashdar Zainal there are various manifestations of the value of religious character education based on the perspective of the Islamic Nusantara tradition, namely (1) love God’s creatures, (2) believe in God’s destiny, (3) spread kindness to others, and (4) attitude of gratitude for God’s giving.Keywords: novel, the value of religious character education, Islam Nusantara Artikel ini mendeskripsikan nilai pendidikan karakter religius novel Sawitri dan Tujuh Pohon Kelahiran karya Mashdar Zainal berdasarkan perspektif tradisi Islam Nusantara. Keberadaan nilai pendidikan karakter religius merupakan aspek yang amat penting untuk diinternalisasikan kepada peserta didik, sebagai upaya membentuk karakter khas dari bangsa Indonesia. Adanya akulturasi antara budaya Jawa dengan tradisi Islam, membawa dampak besar bagi kehidupan masyarakat Jawa. Proses akulturasi tersebut membawa dampak positif bagi keduanya, baik bagi perkembangan Islam maupun budaya Jawa. Sumber data utama penelitian ini berupa teks di dalam novel Sawitri dan Tujuh Pohon Kelahiran yang terkait nilai pendidikan karakter berdasarkan perspektif tradisi Islam Nusantara. Teknik pengumpulan data menggunaan analisis konten (content analysis). Teknik validitas data dengan menggunakan triangulasi sumber data dan triangulasi metode. Model alir Miles dan Huberman, yaitu reduksi data, sajian data, serta penarikan kesimpulan dan verifikasi digunakan sebagai teknik untuk menganalisis data. Hasil penelitian menujukkan bahwa dalam novel Sawitri dan Tujuh Pohon Kelahiran karya Mashdar Zainal terdapat berbagai wujud nilai pendidikan karakter religius berdasarkan perspektif tradisi Islam Nusantara, yaitu (1) mengasihi sesama ciptaan Tuhan, (2) percaya terhadap takdir Tuhan, (3) menebar kebaikan kepada sesama, dan (4) sikap syukur atas pemberian Tuhan.Kata Kunci: novel, nilai pendidikan karakter religius, Islamic Nusantara